THE RATIONALITY OF RELIGIOUS BELIEFS. Issue 40 (9th April 2015) - Frances, Bryan
Abstract : Many highly educated people think religious belief is irrational and unscientific. If you ask a philosopher, however, you'll likely get two answers: most religious belief is rational in some respects and irrational in other respects. In this essay I explain why they think religious belief is rational. In a sequel essay I explain why they think the very same beliefs are irrational.